The Effect of Concentration of Household Waste Liquid Organic Fertilizer and Planting Media on Growth and Production of Cayenne Pepper (Capsicum frutescens L: Efek Konsentrasi Pupuk Organik Cair Limbah Rumah Tangga dan Media Tanam Terhadap Pertumbuhan dan Produksi Tanaman Cabai Rawit (Capsicum frutescens L)” - Mahdalena; Anis Munandar (Universitas Widya Gama Mahakam, 2021)
Effect of Concentration of Household Waste Liquid Organic Fertilizer and Planting Media on Growth and Production of Cayenne Pepper (Capsicum frutescens L)